Perioperative outcomes and long-term quality of life after total pancreatectomy. Issue 13 (8th July 2019) - Pulvirenti, A; Pea, A; Rezaee, N; Gasparini, C; Malleo, G; Weiss, M J; Cameron, J L; Wolfgang, C L; He, J; Salvia, R
Abstract: Background: Total pancreatectomy is required to treat diseases involving the entire pancreas, and is characterized by high morbidity rates and impaired long-term quality of life (QoL). To date, risk factors associated with perioperative and long-term outcomes have not been determined fully. Methods: Data from patients undergoing total pancreatectomy between 2000 and 2014 at two high-volume centres were analysed retrospectively to assess risk factors for major surgical complications. Short Form (SF) 36, European Organisation for Research and Treatment of Cancer QLQ-PAN26 and Audit of Diabetes Dependent questionnaires, as well as an original survey were used to investigate factors influencing QoL. Results: A total of 329 consecutive patients underwent total pancreatectomy in the two centres. Overall, total pancreatectomy was associated with a morbidity rate of 59·3 per cent and a 30-day mortality rate of 2·1 per cent. Age over 65 years and long duration of surgery (more than 420 min) were independently associated with major complications (at least Clavien–Dindo grade III). QoL analysis was available for 94 patients (28·6 per cent) with a median follow-up of 63 (i.q.r. 20–109) months; the most common indication for total pancreatectomy in these patients was intraductal papillary mucinous neoplasms (46 per cent). Both physical (PCS) and mental (MCS) component summary scores of SF-36® were lower after total pancreatectomy compared with scores for a normative population ( P = 0·020 and P < 0·001 respectively). Linear regression analysis showed that young age, abdominal pain and worse perception of body image were negatively associated with the PCS, whereas diabetes, sexual satisfaction and perception of body image affected MCS. Conclusion: Total pancreatectomy can be performed with acceptable morbidity and mortality rates. Older patients had a higher risk of postoperative complications but reported better QoL than younger patients. Graphical Abstract: This study analysed surgical outcomes and long-term quality of life following total pancreatectomy from two high-volume centres for pancreatic surgery. NP, normative population; AP, all patients. Acceptable outcomes in selected patients